Self-Representations of Military Veterans Suffering From Chronic Post-traumatic Stress Disorder: The Role of Sport - Belrose, Celia; Duffaud, Anais; Levy, Dominique; Beji, Aida; Jacob, Sandrine; Lorion, Gregory; Martin-Krumm, Charles; Trousselard, Marion (Frontiers in Psychiatry, 2021)
Background: Post-traumatic stress disorder (PTSD) is a prevalent psychiatric illness in both civilian and military environments. The clinical course,is chronic for a number of patients, especially veterans. Persistent PTSD symptoms interact with representations of the person and their body, and may negatively impact rehabilitation. Sport is known to help psychiatric patients such as those suffering from PTSD, as it improves the connection with the body, and supports physiological regulation. However, the impact of sport on self-representations has not yet been studied. Our first aim is to explore person and body representations in a population of veterans suffering from chronic PTSD, as a function of clinical severity. Second, it explores how a nine-day sport program, which includes socio-professional rehabilitation, changes representations of the person and their body. Methods: This qualitative study examined the self-representation of veterans with chronic PTSD before a sport rehabilitation program. Veterans were given the prompts ‘body’ and ‘person’ and asked to free associate. PTSD severity and the mind–body connection were assessed using validated autoquestionnaires. Parasympathetic activity was recorded at rest. A subgroup of the population volunteered to participate in a post-program session to record the same semantic, psychological, and physiological variables. Results: Although before the program, veterans gave more negatively than positively valenced words, no relation was observed between the overall number of negative words and PTSD severity. Post-program, changes were observed in terms of valence. Specifically, some negatively-valenced categories of words disappeared, and some positive categories appeared. At the same time, there was a fall in PTSD severity, an increase in the mind–body connection, and a decrease in parasympathetic activation. Conclusions: This study highlighted that veterans with chronic PTSD have a negative representation of the self. A dedicated, nine-day program that included regular sport improved self-representations related to both the person and their body, and reduced PTSD symptoms. Sport appears to be a path to the reappropriation of a positive image of the self, by improving the representation of the body.